Aortic Trauma: A Rare Case Report - Rodrigues, Carolina Lacerda; Gaeta, Giovanna Jurucunas de Oliveira; Cruz, Jacqueline Mendes da; da Silva, Felipe Ramon Menezes; Nunes, Thauane Pereira; Santana, Pedro Gomes; Rosati, Ana Paula de Carvalho Miranda; Rosati, Luis Fernando (Brazilian Journal of Case Reports, 2024)
Blunt aortic trauma (BAT) is a rare but critical condition in emergency medicine, with a high mortality rate ranging from 75% to 90%. This trauma typically results from high-energy impacts, such as car accidents, falls from great heights, or severe chest trauma, causing significant damage to the aorta, including lacerations, dissections, intramural hematomas, or even complete aortic rupture. Advanced imaging technologies, such as computed tomography (CT) and transesophageal echocardiography, have recently improved the accuracy of diagnosing aortic injuries, especially in hemodynamically unstable patients. However, the optimal treatment for BAT remains a topic of debate. While endovascular repair is generally preferred due to lower procedural risks and better long-term outcomes, open surgery is still recommended in specific cases, particularly when the injury is extensive or located in critical areas of the aorta, such as the aortic arch. This case report discusses the clinical decisions for a patient with blunt aortic trauma, detailing the choice of open surgery and exploring the challenges of postoperative treatment. Our aim is to contribute to the existing literature by providing insights and recommendations that may assist healthcare professionals in managing similar cases.